The correct subgeneric name of Trypanosoma rangeli Tejera, 1920 (Euglenozoa: Trypanosomatidae), a human-infective endoparasite of neotropical mammals - Molinari, Jesús; Moreno, S. Andrea (Zootaxa, 2018)
Trypanosoma rangeli Tejera, 1920 is peculiar in being transmitted to mammal hosts through the bite of triatomine bugs. For this reason, it has been placed in its own subgenus, Tejeraia Añez, 1982. This name is a junior homonym of Tejeraia Díaz-Ungría, 1963, used for the roundworm Tejeraia mediospiralis (Molin, 1860). The mandatory substitute name of Tejeraia Añez, 1982 is Aneza Özdikmen, 2009. T. (Aneza) rangeli Tejera, 1920 is often referred to as T. (Herpetosoma) rangeli Tejera, 1920. According to nomenclature rules, both name combinations are available. Which one to choose depends on evolutionary and taxonomic considerations. Phylogenetic knowledge indicates that T. (Aneza) rangeli should be used.